Strategi Message Appeals Ono Harato Sebua dalam Kampanye Stop Kekerasan Terhadap Anak - Gus Theodorman Lase; Iskandar Zulkarnain; Mazdalifah Mazdalifah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Wahana Visi Indonesia for the South Nias Program Area is a non-profit organization that carries out a campaign to stop violence against children by using a strategy of message appeals with the nuances of local wisdom, namely ono harato sebua. The research employs a descriptive method using a qualitative approach. Data collection techniques are interviews, observation and documentation. The result shows that the use of message appeals of ono harato sebua in the campaign to stop violence against children, using rational appeals, emotional appeals and morality appeals. The rational appeals use visual media and socialization. Visual media using stickers written on ono harato sebua, and socialization is to convey data on violence against children that occurred in South Nias regency, accompanied by presentation on children’s rights. The emotional appeal that arises is positive emotional appeals, and the moral appeal that appears is the attitude of responsibility and changes in good and right parenting patterns. Barriers that arise during the campaign are personal barriers and environmental barriers. Personal barriers refer to public’s perception of the campaign to stop violence against children, while environmental barriers refer to the indifference and lack of cooperation between community groups in supporting the campaign.